Effect of titanium tetrafluoride varnish on fibroblasts (NIH/3T3): viability assay, morphological analysis and cell signals for apoptotic pathways - Salomão, Priscila Maria Aranda (2018)
Current knowledge supports the application of TiF4 varnish to protect against tooth caries and erosion; however, it is indispensable to know its cytotoxic potential and the mechanism involved on it before applying in patients. Therefore, this study aimed to evaluate 1) The cytotoxic effect of titanium tetrafluoride (TiF4) varnish compared with sodium fluoride (NaF) varnish on murine fibroblast (NIH/3T3), varying the fluoride concentration and time of treatment and 2) The percentage of apoptosis and its mechanism (both mitochondrial mediated by the Bcl-2 family- and death receptorpathways) in human gingival fibroblasts (HGF) and murine fibroblasts (NIH/3T3) treated with TiF4 varnish compared to NaF varnish for 6 h. Step 1) NIH/3T3 were exposed to NaF or TiF4 varnishes containing 0.95, 1.95 or 2.45% F, for 6, 12 or 24 h. MTT viability (n=6) and Hoescht/PI stain assays (n=3) as well as the cells morphology (HE, only for 24 h, n=3) and stiffness (AFM, only for 2.45% F, 6 or 12 h) were analyzed. Both varnishes, at 1.90 and 2.45% F, reduced cells viability by similar extent (33-86% at 6 h, 35-93% at 12 h, and 87-98% at 24 h) compared to control, regardless of the type of fluoride. TiF4 and NaF (2.45% F) reduced cell stiffness to a similar extent, but only TiF4 differed from control. Step 2) HGF and NIH/3T3 were exposed to NaF or TiF4 (2.45% F) varnishes for 6 h. Cells were examined by the TUNEL method using fluorescence microscope. The caspases-3, -8 and -9 activities were assessed. The cDNA for cytocrome c, Bax, Bad, Bcl-2, VDAC-1 and Fas-L was amplified by quantitative PCR (qPCR). Bax, Bcl-2 and Fas-L were further detected by western blot. Both fluorides similarly increased the percentage of apoptosis, while they failed in activating caspases-3, -8 and -9 for both types of cells. Bax/Bcl-2 ratio, cytochrome C and VDAC-1 gene expressions were not altered by both fluoride treatments. However, NaF varnish increased the amplification of Fas-L gene for NIH/3T3 and HGF, while TiF4 varnish induced lower Bad/Bcl-2 ratio expression compared to control for NIH/3T3, but not for HGF. No effect of the fluorides was detected in the proteins analysis. TiF4 and NaF have similar cytotoxicity on NIH/3T3, which is dependent on the F concentration and the exposure time. Both fluorides, at the studied conditions, similarly induce a low percentage of apoptosis, with consequent modest activation of Bcl-2 and Fas-L-dependent signaling pathways.